2014
DOI: 10.4172/2329-9096.1000206
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of EMG Signals from Surface and Fine-Wire Electrodes During Shoulder Abduction

Abstract: Electromyography quantifies the action of muscles and the data provides an understanding of how coordination occurs during an action. This concurrent comparison research study evaluated electromyography signals from surface and fine-wire electrodes placed simultaneously on selected shoulder muscles. A stand-alone data logger collected electromyography signals from both types of electrodes placed on and within the teres major, supraspinatus, infraspinatus and posterior deltoid muscles as 30 healthy adult subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…First, the value of using surface EMG electrodes for the measurement of shoulder muscles has been questioned. 18,19 However, the authors feel that any error introduced by using surface electrodes would be equal for each exercise trial since the data were case-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…First, the value of using surface EMG electrodes for the measurement of shoulder muscles has been questioned. 18,19 However, the authors feel that any error introduced by using surface electrodes would be equal for each exercise trial since the data were case-controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Chimera et al found no electrode differences in onset timings within the plantarflexors during walking . In contrast, Rajaratnam et al found poor relationships in contraction onset between electrode types in smaller deep muscles (infraspinatus, supraspinatus, and teres major; r = ‐0.01–0.07) and excellent relationships for larger muscles (posterior deltoid; r = 0.94) during shoulder abduction. Possibly due to improper instrumentation in that study, cross‐talk from the larger posterior deltoid likely obscured the sEMG recording of the smaller muscles, causing false onsets.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4 Reasonable correlations between sEMG and fwEMG were found in the lower limb during walking, 16 while inconsistent correlations were found in shoulder muscles during abduction. 17 The fwEMG and ultrasound onset were inconsistent with each other, 11,13,18 while others have reported moderate relationships between sEMG and ultrasound onset. 14 Differences in muscles, contraction tasks, and experimental designs (e.g., number of repetitions, averaging methods) may explain specific levels of agreement between studies; however, during a re-analysis of published EMG-and ultrasound-derived contraction onset studies, Dieterich et al 18 noted a surprisingly high number of trials within each study (17-72%) where ultrasound onset was detected before electrical activation.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, the design of the electrodes, the distance between them, and the placement and the orientation of them along the muscle affect signal fidelity. Furthermore, the quality of the contact between the electrodes and the skin, the wire length to the amplifier, the characteristics between the electrodes [4], the amplifier unit, and the signal processing methods are also important. There are many factors which can influence the EMG signal on the subject side as well, such as the conditions of the muscles.…”
Section: Introductionmentioning
confidence: 99%